Performance and carcass characteristics of different cattle types—A preliminary report - H.J. Tuma; Dell M. Allen; M.L. May; M.D. Albrecht; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1972)
This report contains results from the U.S. Meat Animal Research Center Cattle Germ Plasm Evaluation Program. Dr. Keith Gregory and Dr. Hudson Glimp, U.S. Meat Animal Research Center, Clay Center, Nebraska, initiated and designed the cattle germ plasm evaluation program. Kansas State University and the Livestock Division, C&MS, U.S.D.A. are cooperating on the project.
Keywords: Cattlemen& #x27; s Day; 1972; Report of progress (Kansas State University. Agricultural Experiment Station); 557; Beef; Performance; Carcass characteristics